Indian Ethos Echoes in Management - Kansal, Mani (Journal of Commerce and Trade, 2009)
A Hindu Perspective on Religion and Management. It could of course be argued that there are good prudential reasons for preferring the word “spirituality” to “religion”. In a recent probe of the attitudes of several hundred managers, only 30 percent had a positive view of religion and spirituality. More than half, 60 percent, had a positive view of spirituality and a negative view of religion. In the case of Hinduism, however, although prudential concerns apply, other reasons also come into play. It could be plausibly argued that Hinduism is better described as a “spirituality” or “wisdom” rather than religion in the Western sense, a tendency which is already apparent in attempts to describe it as a “state of mind,” and even the “mind of India.” The title, therefore, appropriate as it is, is particularly apposite in the case of Hinduism. Thus rather than why spirituality, the first question one must address is: What is Spirituality? The core issue now changes from how our relationship with fellow human beings bears on management - which has to do with morality, into one of how our relationship to ultimate reality bears on management – which has to do with spirituality. I am not arguing that the two dimensions may not overlap and may even be interconnected; I would however like to maintain that they are analytically distinguishable.